Application of herbal flour ingredients in the Duck Livestock Group, Sumber Rejeki, Kediri Regency - Mubarak Akbar; Efi Rokana; Edy Soenyoto (Community Empowerment, 2022)
Some residents of Dawung Village in Ringinrejo District, Kediri Regency work as duck breeders. Many breeders are dissatisfied with the government's policy prohibiting the use of Antibiotic Growth Promoter (AGP) in animal feed, resulting in decreased livestock production. The goal of this program is to improve the standard of living and productivity of duck breeders by teaching them how to make herbal flour that can be mixed into duck feed instead of antibiotics. The diffusion of science and technology is the method employed. The availability of feed containing herbal flour additives is a outcome of this program. Another benefit is a greater understanding and knowledge of herbal flours as antibiotic substitutes that are safer for animal feed.